Elective caesarean section cost efficiency with time-driven activity-based costing - Fahmy Abdul Haq; Firman Pribadi; Akrom Akrom (International Journal of Public Health Science (IJPHS), 2023)
Hospitals compete to increase the value of services, one of which is cost-efficiency. The complexity of the service process and many resources in health services make calculating costs difficult. Time-driven activity based costing (TDABC) can identify specific cost drivers so that it has the potential to help identify inefficient processes. This study analyzes the cost efficiency of caesarean section with the TDABC. This study uses a qualitative research design with a case study method at one of the hospitals in Bantul, Yogyakarta, Indonesia. Primary data was taken from direct observation and interviewing hospital staff. Secondary data were obtained from hospital annual report 2019, hospital financial reports 2019, and patient medical records. The cost of a caesarean section was calculated and analyzed using the seven-step TDABC model with one-year hospital 2019 data. The cost of an elective caesarean section with the TDABC method is IDR 4,576,182.72. Hospitals can reduce postoperative costs by 25% by reducing the use of medicine and antibiotics. Based on the research results, TDABC can properly analyze costs based on services and identify inefficient processes.